Astragalin Promotes Osteoblastic Differentiation in MC3T3-E1 Cells and Bone Formation in vivo - Liu, Li; Wang, Dan; Qin, Yao; Xu, Maolei; Zhou, Ling; Xu, Wenjuan; Liu, Xiaona; Ye, Lei; Yue, Shijun; Zheng, Qiusheng; Li, Defang (Frontiers in Endocrinology, 2019)
Astragalin (AG) is a biologically active flavonoid compound that can be extracted from a number of medicinal plants. However, the effects of AG on osteoblastic differentiation in mouse MC3T3-E1 cells and on bone formation in vivo have not been studied fully. In this study, we found that the activities of alkaline phosphatase (ALP) and mineralized nodules in MC3T3-E1 cells were both significantly increased after treatment with AG (5, 10 and 20 μM). Meanwhile, the mRNA and protein levels of osteoblastic marker genes in MC3T3-E1 cells after AG treatment were markedly increased compared with a control group. In addition, the levels of BMP-2, p-Smad1/5/9, and Runx2 were significantly elevated in AG-treated MC3T3-E1 cells. Moreover, we found that the protein levels of Erk1/2, p-Erk1/2, p38, p-p38, and p-JNK were also significantly increased in AG-treated MC3T3-E1 cells compared to those in the control group. Finally, in vivo experiments demonstrated that AG significantly promoted bone formation in an ovariectomized (OVX)-induced osteoporotic mouse model. This was evidenced by significant increases in the values of osteoblast-related parameters (BFR/BS, MAR, Ob.S/BS and Ob.N/B.Pm) and bone histomorphometric parameters (BMD, BV/TV, Tb.Th and Tb.N.) in OVX mice after AG treatment (5, 10, and 20 mg/kg). Collectively, these results demonstrated that AG may promote osteoblastic differentiation in MC3T3-E1 cells via the activation of the BMP and MAPK pathways and promote bone formation in vivo. These novel findings indicated that AG may be a useful bone anabolic agent for the prevention and treatment of osteoporosis.